Automated character recognition and inspection - Leu, Yew Seng. (2009)
Character Recognition has been a popular focus of pattern recognition research since at least the 1920s. The continuing challenge of commercially viable recognition has kept character recognition research ongoing. How does the human brain recognize different characters ? Which part of the character is it looking for ? What kinds of features do we get when we see a character ? Is there some way we can extract character recognition knowledge from humans, who have become such superb character recognizers